Effect of Surgeon Handedness on Coronal Alignment in Total Knee Arthroplasty - Chaiyamahapruek, MD, Opas (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To study the effect of surgeon handedness by comparing coronal alignment in total knee arthroplasty (TKA) between left and right sides. Methods: This study retrospectively reviewed the medical records and knee radiographs of patients who underwent total knee arthroplasty using conventional techniques from 2010 to 2012. There were 49 right knees and 47 left knees in 78 patients. The knee radiographs taken before and after surgery were used to measure the tibiofemoral angle and the coronal alignment of the femoral and tibial components. A value within the optimum ±3º was defined as “acceptable” and a value over the optimum ±3º was defined as an “outlier”. Results: The postoperative tibiofemoral angle showed outliers in 7 right TKAs and 11 left TKAs. The coronal alignment of the femoral component showed outliers in 9 right TKAs and 7 left TKAs. The coronal alignment of the tibial component showed outliers in 2 right TKAs and 10 left TKAs. There was a significant difference in the outliers of coronal alignment of the tibial component between right and left TKAs. Conclusion: Surgeon handedness affects the coronal alignment of the tibial component. There were more outliers of the coronal alignment of the tibial component in left knees when performed by right-handed surgeons.